2019
DOI: 10.1073/pnas.1903866116
|View full text |Cite
|
Sign up to set email alerts
|

Climatic shifts drove major contractions in avian latitudinal distributions throughout the Cenozoic

Abstract: Many higher level avian clades are restricted to Earth’s lower latitudes, leading to historical biogeographic reconstructions favoring a Gondwanan origin of crown birds and numerous deep subclades. However, several such “tropical-restricted” clades (TRCs) are represented by stem-lineage fossils well outside the ranges of their closest living relatives, often on northern continents. To assess the drivers of these geographic disjunctions, we combined ecological niche modeling, paleoclimate models, and the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 83 publications
(70 reference statements)
3
47
0
Order By: Relevance
“…Analyses controlling for sampling bias have suggested that, for many groups, the LDG was less marked in the past than it is today (i.e., with similar species diversity across latitudes) or even developed a paleotemperate peak during some periods (see Mannion et al 2014 for a review). This sampling-corrected flattened LDG in deep time has been demonstrated for nonavian dinosaurs (Mannion et al 2012), mammals (Rose et al 2011;Marcot et al 2016), birds (Saupe et al 2019a), tetrapods (Brocklehurst et al 2017), Warm-equable regimes got then restricted to the equator. The LDG evolved following these global changes; during greenhouse periods diversity was similar across latitudes, such that the LDG flattened, whereas in cold periods diversity peaked at the equator (a steep LDG) (Mannion et al 2014).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Analyses controlling for sampling bias have suggested that, for many groups, the LDG was less marked in the past than it is today (i.e., with similar species diversity across latitudes) or even developed a paleotemperate peak during some periods (see Mannion et al 2014 for a review). This sampling-corrected flattened LDG in deep time has been demonstrated for nonavian dinosaurs (Mannion et al 2012), mammals (Rose et al 2011;Marcot et al 2016), birds (Saupe et al 2019a), tetrapods (Brocklehurst et al 2017), Warm-equable regimes got then restricted to the equator. The LDG evolved following these global changes; during greenhouse periods diversity was similar across latitudes, such that the LDG flattened, whereas in cold periods diversity peaked at the equator (a steep LDG) (Mannion et al 2014).…”
mentioning
confidence: 60%
“…More ancient extinctions have also been considered (Latham and Ricklefs 1993;Markwick 1998;Roy and Pandolfi 2005;Hawkins et al 2006;Weir and Schluter 2007;Dunn et al 2009;Eiserhardt et al 2015;Pulido-Santacruz and Weir 2016). For example, recent studies suggested the avian LDG resulted from the differential extirpation of older warm-adapted clades from the temperate regions newly formed in the Neogene (Hawkins et al 2006;Pulido-Santacruz and Weir 2016;Saupe et al 2019a). Pyron (2014) suggested that higher temperate extinction represents a dominant force for the origin of LDG in lepidosaurs.…”
mentioning
confidence: 99%
“…The appearance of the Antarctic Circumpolar Current strengthened climatic gradients leading to more pronounced seasonality at high latitudes (Eldrett et al 2009). Fossil evidence indicates extirpation and contraction of “tropical-like” faunas and floras towards equatorial latitudes (Saupe et al 2019, Meseguer & Condamine 2019) and concomitant ecological turnover (Meng & McKenna 1998). We found that the contributions of the Nearctic and Palearctic fauna to global nymphalid lineage diversity were lowest during the Eocene (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Dispersal into other regions was probably a result of tracking tropical habitat southward [13]. This phenomenon is attributed to a steepening latitudinal climate gradient by the end of the Eocene [26,114,115], precipitated by the opening of the Drake Passage [116]. Within Eurasia, the uplift of the Himalayas [117] starting in the early Eocene, and the closure of the Turgai Strait between northern Africa and Asia at the end of the Eocene [118], significantly impacted climate and biomes of a once subtropical Eurasia.…”
Section: Discussionmentioning
confidence: 99%